Optimalisasi Pengolahan Buah Tomat Menjadi Kurma Tomat Sebagai Upaya Peningkatan Nilai Tambah Produk Hortikultura - Hais Dama; Idham M. Ishak; Meryana Francissca Dungga (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
Luwoo Village, Telaga Jaya Subdistrict, Gorontalo Regency is a major tomato-producing area, with approximately 35 hectares under cultivation and an average yield of 10-12 tons per hectare per harvest season. Because tomatoes are highly perishable due to their high moisture content, market oversupply during peak harvest frequently drives prices below IDR 20,000 per 7-kg sack, leaving a considerable share of the harvest to rot. This condition is compounded by farmers' limited knowledge of and access to postharvest processing technology, so that tomatoes are sold almost exclusively as fresh produce without any derivative diversification. This community service program aimed to strengthen the knowledge and skills of the Luwoo Village community in converting surplus tomatoes into “tomato dates” (kurma tomat), a shelf-stable candied product with higher economic value, through hands-on training in sorting, blanching, sugar-syrup cooking, and drying, complemented by micro-enterprise management and marketing mentoring. The activity was conducted in August 2025 in Luwoo Village and involved 24 participants drawn from the Farmer Women's Group (KWT) and village youth. The implementation method comprised community socialization, technical production training, provision of simple processing equipment, business management and branding training, digital and conventional marketing training, and an evaluation based on pre-tests and post-tests measured against predetermined success criteria. The results show a marked improvement in participants' understanding of tomato postharvest processing techniques, with average knowledge scores rising from the “poor” to the “good” category, and the successful production of a branded product, “Kurmato Luwoo,” packaged under hygienic conditions. Most participants were able to produce tomato dates that met the targeted quality standard. The program is expected to reduce the economic losses caused by tomato spoilage, strengthen the institutional capacity of the farmer and youth groups, and support the national food-security agenda through the development of local potential.